Outcome Of Repair Of Inguinal Hernia In Adult : Comparison Between General Versus Local Anesthesia - Younis, Azhar Mohammed; Ali, Ali Jumaah; Mohammed, Mohammed Hasan (Scientific Journal of Medical Research, 2021)
Objectives: Inguinal hernia repair is a common surgical procedure can be performed under general, Local, depending on personal, medical, economic factors, choosing anesthesia is reflected on expenses and postoperative morbidity, so the technique must be easy to perform and practice that achieve patient satisfaction with low recurrence rate and complication. Methods: Our study composed of 60 patient, all patient of the study were male, divided into two groups, each with 30 patient according to type of anesthesia, group A repair under general anesthesia (GA), group B repair under local anesthesia (LA), after taking singed consent formed, age of patient for general anesthesia ranged from 45-70 years ,compared to (20- 70) years for local anesthesia group. Results: A total of 60 patients had inguinal hernia repair in this study, the right inguinal hernia was 80% present (48 patients), and 20% was left inguinal hernia (12 cases), present for direct inguinal hernia was 53.3% (16 cases of study), for indirect hernia 26.6%( 8 cases of study ) and 20%percent (6cases) for both direct and in direct hernia, Mean of age for general anesthesia group patients was 44.73 with median age 45, while for local anesthesia group mean age was 66.07 with median 66, mean-time of surgery for patients under local anesthesia equal to 45.92. It was lower significantly compared to 48.45 for the general anesthesia group. All patients of inguinal hernia with local anesthesia group were discharged home on the same operative day; four general anesthesia group patients were discharged on the first postoperative day. Regarding postoperative surgical complications more in general anesthesia than local (postoperative nausea, vomiting, cough, headache, retention of urine, respiratory and cardiovascular). Conclusion: The use of local anesthesia in inguinal hernia repair safe, cost-effective, with less hospital stay, less postoperative respiratory and cardiovascular complications compared to general anesthesia, mainly in a patient with an underlying cardiopulmonary disease that is affected by general anesthesia, addition to the shorter time of surgery. And they are reducing surgical waiting list.